2020
DOI: 10.5565/publmat6422007
|View full text |Cite
|
Sign up to set email alerts
|

The ascent-descent property for $2$-term silting complexes

Abstract: We will prove that over commutative rings the silting property of 2-term complexes induced by morphisms between projective modules is preserved and reflected by faithfully flat extensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
(44 reference statements)
1
7
0
Order By: Relevance
“…It should be noted that in Example 2.6, in the paper [15] by Breaz, a similar phenomenon is exhibited to those studied in our paper, but for a different problem.…”
Section: Silting Complexessupporting
confidence: 86%
“…It should be noted that in Example 2.6, in the paper [15] by Breaz, a similar phenomenon is exhibited to those studied in our paper, but for a different problem.…”
Section: Silting Complexessupporting
confidence: 86%
“…The behaviour of (co)silting modules under ring extensions has been studied in [12]. In particular, it was shown that over commutative rings every silting module extends to a silting module.…”
Section: Ascent Of Minimalitymentioning
confidence: 99%
“…Of course, if λ : R → S is surjective with kernel I, then every silting right R-module T verifies the condition T ⊗ R S ≃ T /T I ∈ GenT and therefore extends to a silting S-module T ⊗ R S, cf. [12,Corollary 2.4]. In general, however, the condition in the theorem above can fail, even when T is minimal.…”
Section: Ascent Of Minimalitymentioning
confidence: 99%
See 1 more Smart Citation
“…It is already known that the properties of being projective, 1-tilting and 2-silting are ad-properties (cf. [29], [19], and [8]). The Zariski locality for ntilting modules was also proved in [19].…”
Section: Introductionmentioning
confidence: 99%